2016
DOI: 10.1002/aic.15503
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of NO and SO2 using aqueous peroxymonosulfate with coactivation of Cu2+/Fe3+ and high temperature

Abstract: A novel process on simultaneous removal of NO and SO2 using aqueous peroxymonosulfate (PMS) with synergic activation of Cu2+/Fe3+ and high temperature in an impinging stream reactor is developed for the first time. Effects of PMS concentration, Cu2+/Fe3+ concentration, reaction temperature, solution pH, flue gas flow, liquid–gas ratio, gas components, and inorganic ions on NO/SO2 removals were investigated. Active species and products were determined by electron spin resonance spectroscopy and ion chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
108
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 35 publications
2
108
1
Order By: Relevance
“…Peroxymonosulfate (PMS) is a water‐soluble, environmentally friendly, safe to handle and stable oxidant . Especially as a solid oxidant, PMS has a big advantage in concentrating the products (when solid oxidizer is added, no water is simultaneously carried), and it is also much easier to transport and store than commercial H 2 O 2 solution, with a much higher security . In the past several years, PMS‐based oxidation technologies have been widely studied in water treatment area .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Peroxymonosulfate (PMS) is a water‐soluble, environmentally friendly, safe to handle and stable oxidant . Especially as a solid oxidant, PMS has a big advantage in concentrating the products (when solid oxidizer is added, no water is simultaneously carried), and it is also much easier to transport and store than commercial H 2 O 2 solution, with a much higher security . In the past several years, PMS‐based oxidation technologies have been widely studied in water treatment area .…”
Section: Introductionmentioning
confidence: 99%
“…In the area of flue gas purification, Adewuyi and Owusu developed the oxidation removal process of nitric oxide via aqueous solutions of PMS in a bubble column reactor and made a systematic study for the operating parameters and absorption rates of nitric oxide removal. Recently, Liu et al reported the removals of NO and SO 2 using aqueous PMS with independent or synergic activation of transition metal ions, heat, UV light, and ultrasound in a variety of gas–liquid reactors. Among these methods, transition metal ions activation technologies show excellent development potential for NO and SO 2 removals because of simple process/device and low costs .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large‐scale emissions of sulfur dioxide (SO 2 ) and nitric oxides (NO x ) from coal‐fired flue gas have caused serious environmental pollution issues, such as acid rain, photochemical smog and regional haze . Currently, the mainstream removal technologies for SO 2 and NO x are limestone‐based wet flue gas desulfurization (Ca‐WFGD) and ammonia‐based selective reduction (NH 3 ‐SCR), respectively, in coal‐fired power plants .…”
Section: Introductionmentioning
confidence: 99%